A multivariate analysis of morphometric and exosomatic characters of Iguanid Lizards of the Patagonian Liolaemus kingi complex - Scolaro, José Alejandro (1987)
For more than a century Liolaemus kingi (Bell, 1843) has been reported as a classical viviparous Patagonian iguanid, widely distributed in southern Chubut and Santa Cruz Provinces (Cei, 1975). In addition to the nominate form, two other localized forms of this group have been discovered (Cei and Scolaro, 1981, 1983). Paying attention to their morphological similarities with L. kingi kingi, and pointing out the quite evident condition of allopatry in both cases, the authors described L. kingi somuncurae and L. kingi baguali as subspecies, from the Somuncurá plateau of Rio Negro, and the Sierra Bagual, Santa Cruz, respectively. However, their peculiar physiognomy and the specialized conditions of the habitats justified additional research on morphological and evolutionary relationships of these still poorly known tropidurine lizards. We here assess the reciprocal position of the members of the L. kingi complex by means of multivariate analysis of their morphometric and exosomatic characters.